Repurposing of Clinical Drugs as Negative Allosteric Modulators for the Human 5-HT3A Receptor - Rodriguez Araujo, Noelia (2024)
Drug repurposing offers a rational approach to reducing the time and costs associated with developing new therapies. In this study, piperazine (PZE), an anthelmintic drug, and hydroxyzine (HZE), a first-generation H1 receptor antagonist and derivative of PZE, were evaluated as novel modulators of the human 5-HT3A receptor. This receptor belongs to pentameric ligand-gated ion channel family and has gained interest as a pharmacological target for neurological, psychiatric, and gastrointestinal disorders. HEK293 cells were transfected with 5-HT3A receptor cDNA, and electrophysiological analyses were subsequently conducted. Whole-cell recordings revealed that preincubation with PZE or HZE inhibited 5-HT-evoked currents in 5-HT3A receptors, with HZE showing greater potency than PZE. Notably, co-application of either compound with 5-HT did not alter the peak current, suggesting a non-competitive inhibition mechanism. PZE also increased the EC50 value and reduced the maximum 5-HT response, supporting as a negative allosteric modulator (NAM). Molecular docking studies further indicated two primary binding sites for PZE and HZE within the 5-HT3A receptor, separate from the 5-HT binding site, supporting their roles as potential NAMs. These binding sites were identified at the interface between the transmembrane (TMD) and the extracellular domains, as well as at the top of the TMD. Based on the potential interactions of the drugs with the residues, two amino acids were selected from each binding site and were mutated to confirm their contribution. For the first analyzed mutant, a change in the inhibition mediated by HZE was detected, thus suggesting its contribution to the allosteric modulation. This drug repurposing strategy provides a rational and efficient pathway to explore new therapeutic applications for clinically approved drugs by identifying alternative targets and their mechanisms.